2023
DOI: 10.1186/s12891-023-06370-5
|View full text |Cite|
|
Sign up to set email alerts
|

Associations between blood antioxidant levels and femoral neck strength

Abstract: Background Studies have confirmed that antioxidants contribute to a lower risk of osteoporosis, which is an independent factor for femoral neck fracture (FNF). However, the associations between blood antioxidant levels and femoral neck strength remain unclear. Objective Our aim was to test the hypothesis that levels of blood antioxidants are positively associated with composite indices of bone strength in femoral neck, which integrate the bending s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It has been suggested by previous studies that antioxidant intake has a strong impact on the femoral neck BMD. 57,58 For instance, β-carotene intake had a negative association with femoral neck and total hip BMD rather than lumbar spine BMD in premenopausal women. 58 Furthermore, the interesting observation warrants validation in a more extensive population cohort.…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested by previous studies that antioxidant intake has a strong impact on the femoral neck BMD. 57,58 For instance, β-carotene intake had a negative association with femoral neck and total hip BMD rather than lumbar spine BMD in premenopausal women. 58 Furthermore, the interesting observation warrants validation in a more extensive population cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Niu et al found a positive correlation between high blood zeaxanthin levels and femoral neck strength. Moreover, a positive correlation was found between the blood zeaxanthin level and other bone strength parameters, such as bending strength index, compression strength index, and impact strength index [ 93 ]. In another study, Murphy et al, analyzing 4513 community-dwelling adults aged >50 years, found that subjects with higher lutein and zeaxanthin serum levels were less likely to develop frailty after 8 years of follow-up.…”
Section: Nutraceuticalsmentioning
confidence: 99%
“…Fenugreek seeds contain phosphorus, which falls into different classes: inorganic phosphorus, phospholipids, phytates, phosphorproteins, and nucleic acids. Germinated seeds contain amino acids, proteins, ascorbic acid, vitamin E, and sugars [4][5][6][7]. A previous study showed that mandibular fracture healing had been accelerated in camels fed fenugreek (100 g/camel/day) for two weeks [3].…”
Section: Introductionmentioning
confidence: 99%